A randomized study to compare extracorporeal shockwave lithotripsy with or without intravenous anaesthesia - Gupta, Neeraj; Chanchlani, Roshan; Tiwari, Punit (International Surgery Journal, 2016)
Background:The lifetime prevalence of kidney stone disease is estimated at 1-15%. The various treatment options available for urinary calculus disease are open surgery, ureterorenoscopy, percutaneous nephron-lithotomy retrograde intra-renal surgery & extracorporeal shock wave lithotripsy. The aim of the study was to study whether performing extracorporeal shockwave lithotripsy (ESWL) under intravenous anesthesia can reduce no. of sessions by increasing intensity of shockwaves and its comparison with ESWL under local anesthesia and also to study the safety of higher intensity shock waves. Methods: The nucleus of this prospective study done between March 2011 to February 2015 was 60 patients with renal or upper ureteric solitary calculus less than or equal to 2 cm in size, in which ESWL is elected as the treatment. These were randomized into one of the two groups with 30 patients in each - Group I: in which patients underwent ESWL under IV anesthesia & group II: in which patients underwent ESWL under local anesthesia. Results:For age group, P value of age difference of the two groups was 0.6 and not significant. During the study it was found that there was statistically significant reduction in number of sessions required for complete stone clearance in Group I. In group I the average number of shock waves used was 3800, whereas in group II it was 5967. The P value of difference between the means was extremely significant (P =0.003). Time taken for clearance of stone in group I was 1 month in 22 patients and 3 months in 8 patients with the average being 1.53. In group II time taken for clearance was 1 month in 9 patients and 3 months in 21 patients and the mean was 2.4. Conclusions:The use of total intravenous anesthesia (TIVA) for ESWL reduces the number of sessions significantly by allowing higher intensity and number of shock waves & improved fragmentation due to regular and controlled respiratory excursions, and immobility of the patient, leading to significantly less wastage of shockwaves when compared to ESWL without TIVA.